IMPLEMENTING CLIL AT THE TECHNICAL DIPLOMA LEVEL: CHALLENGES AND ADAPTATIONS IN A KERALA CONTEXT - George, Arun (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Content and Language Integrated Learning (CLIL) method presents a compelling approach to addressing deficiencies in both content mastery and language proficiency, particularly in contexts where communication skills impact subject learning. The research conducted in the Technical Diploma stream in Kerala provides insightful observations into the practical implementation of CLIL in a challenging educational environment. The researcher faced difficulties in aligning CLIL strategies with the existing curriculum and managing rigid, overcrowded classrooms, which hampered interactive and communicative teaching methods. While theoretical aspects of CLIL provided a solid foundation, practical implementation revealed gaps between theory and the realities of the local educational environment. The successful adaptation of CLIL required modifications to the traditional Preparation, Activity, and Revision (PAR) sessions, effectively balancing content and language acquisition despite the constraints. This approach led to noticeable improvements in student engagement and learning outcomes, demonstrating that CLIL can be effective when tailored to meet the specific needs of the educational setting.